TESTING ANTITHROMBIN LEVEL ALLOWS PREDICTING A CLINICAL OUTCOME OF SEPSIS - I. V. Redkin; A. F. Lopаtin; Yu. V. Skripkin; V. V. Sаmoylenko; V. V. Likhvаntsev (Вестник анестезиологии и реаниматологии)
Antithrombin is one of the key regulating factors of homeostasis, which activity significantly reduces in SIRS.The objective of the study: to investigate possibility and feasibility to test antithrombin level in blood plasma in order to predict treatment outcomes in patients with sepsis.Subjects. The level of antithrombin was tested in 83 patients by the start and at the peak of the disease. Predictive value was compared for antithrombin tests, some other parameters of coagulogram, and clinical severity scales in sepsis.Results. On the 5th day of the disease, the most significant predictors of the unfavorable outcome of sepsis were identified: fibrinogen level (Odds ratio – 2.42 [0.92–6.33]; p = 0.0722); and antithrombin level (Odds ratio – 26.4 [8.02 86.86]; p < 0.0001).Pair-wise comparison of ROC-curves of fibrinogen and antithrombin at the final point of the study demonstrated differences between areas under curve (AUC), which made 0.337 [95% CI 0.154–0.520] with p = 0.0003, which confirmed the assumption of the high predictive value of antithrombin level. With the cut-off point at ≤ 61% this test demonstrated the sensitivity and specificity of 79% and 88% respectively.Conclusion: In order to predict severity and potential outcome of sepsis, it is recommended to test antithrombin level at the peak of the disease.